Developing listening skill in children for communication, interaction and learning (2010)
It is obvious that of all the language skills that children develop, listening is the one developed earliest and practised most frequently. As much as 80 percent of the information learners obtain is the result of listening, yet listening has suffered much neglect, and taught least often in the classroom and had been referred to as the neglected or forgotten language art, in spite of the benefits that can accrue from it. Where listening and speaking are taught, both skills are viewed and taught as a different discrete skills. However, 1980s and 1990s have witnessed a paradigm improvement in the teaching of listening and speaking skills with the integration of both listening and speaking skills as one communicative process called oral communication or oral language. This paper examined the concept of listening skill, its development as interactive and communicative processes in children, the benefits that both listening and speaking skills have on children’s language, intellectual, social, academic and emotional development. Problems militating against development of listening skill were also identified and suggestions on how to help children develop their oral communication were made.